2005
DOI: 10.1002/elps.200500178
|View full text |Cite
|
Sign up to set email alerts
|

Application of an external contactless conductivity detector for the analysis of beverages by microchip capillary electrophoresis

Abstract: Quantitative total ionic analysis of alcoholic and nonalcoholic beverages was performed by microchip capillary electrophoresis with external contactless conductivity detection. An electrolyte solution consisting of 10.5 mM histidine, 50 mM acetic acid, and 2 mM 18-crown-6 at pH 4.1 was used for the determination of NH(4) (+), K(+), Ca(2+), Na(+), and Mg(2+). Fast analysis of Cl(-), NO(3) (-), and SO(4) (2-) was achieved in 20 mM 2-(N-morpholino)ethanesulfonic acid /histidine electrolyte solution at pH 6.0 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
2
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 40 publications
2
37
2
1
Order By: Relevance
“…As expected, the LOD obtained by our chip is lower than those results obtained from chips with similar electrode geometry, thicker insulating layers and operated at low excitation frequencies, [24][25][26] as shown in Table 1. While it is higher than the results reported by Kubaň and Hauser,8,16,27 the excitation frequencies used in their work (500 kHz, 8 530 kHz, 16 600 kHz 27 ) are much higher than our applied frequency of 60 kHz and the range of the detector (0-300 kHz) used here, which is in line with the conclusion that the output of the detector increased sharply between 400 and 600 kHz. 13 Moreover, the LODs in their work were obtained when the optimized electrode geometry was used, and it has also been demonstrated that the electrode geometry had a significant effect on the sensitivity.…”
Section: Characteristics Of the Microchipsupporting
confidence: 88%
See 1 more Smart Citation
“…As expected, the LOD obtained by our chip is lower than those results obtained from chips with similar electrode geometry, thicker insulating layers and operated at low excitation frequencies, [24][25][26] as shown in Table 1. While it is higher than the results reported by Kubaň and Hauser,8,16,27 the excitation frequencies used in their work (500 kHz, 8 530 kHz, 16 600 kHz 27 ) are much higher than our applied frequency of 60 kHz and the range of the detector (0-300 kHz) used here, which is in line with the conclusion that the output of the detector increased sharply between 400 and 600 kHz. 13 Moreover, the LODs in their work were obtained when the optimized electrode geometry was used, and it has also been demonstrated that the electrode geometry had a significant effect on the sensitivity.…”
Section: Characteristics Of the Microchipsupporting
confidence: 88%
“…8,16,[24][25][26][27] Based on the signal-to-noise ratio of 3, the LOD for Na + was 1.25 mg ml À1 by using our system. As expected, the LOD obtained by our chip is lower than those results obtained from chips with similar electrode geometry, thicker insulating layers and operated at low excitation frequencies, [24][25][26] as shown in Table 1.…”
Section: Characteristics Of the Microchipmentioning
confidence: 95%
“…Poly(methyl methacrylate) (PMMA) microchips have recently been used in combination with C 4 D for the determination of anions and cations [116] and food additives [76] in beverages.…”
Section: Microchips and Other Future Trends In Food Analysismentioning
confidence: 99%
“…Therefore, a substantial number of publications dealing with this topic can be found in the literature, as can be seen from recent review articles [5][6][7]. An overview of CE applications in this field, published since 2003, is given in Table 1. CE and CEC methods for the determination of organic acids in a variety of beverages including fruit juices [27][28][29][30][31][32], beer [32,33], wines [27,30,[34][35][36][37][38], milk [39], and coffee [40,41] have been reported in the recent literature. Using a CZE method with coelectroosmotic conditions, Mato et al [27] succeeded in the simultaneous analysis of 16 organic acids in beverages in less than 3.5 min.…”
Section: Organic Acids In Food and Beveragesmentioning
confidence: 99%